Defense of pyrethrum flowers: repelling herbivores and recruiting carnivores by producing aphid alarm pheromone. Issue 3 (31st May 2019) - Li, Jinjin; Hu, Hao; Mao, Jing; Yu, Lu; Stoopen, Geert; Wang, Manqun; Mumm, Roland; de Ruijter, Norbert C. A.; Dicke, Marcel; Jongsma, Maarten A.; Wang, Caiyun
Summary: ( E )‐β‐Farnesene (EβF) is the predominant constituent of the alarm pheromone of most aphid pest species. Moreover, natural enemies of aphids use EβF to locate their aphid prey. Some plant species emit EβF, potentially as a defense against aphids, but field demonstrations are lacking. Here, we present field and laboratory studies of flower defense showing that ladybird beetles are predominantly attracted to young stage‐2 pyrethrum flowers that emitted the highest and purest levels of EβF. By contrast, aphids were repelled by EβF emitted by S2 pyrethrum flowers. Although peach aphids can adapt to pyrethrum plants in the laboratory, aphids were not recorded in the field. Pyrethrum's (E)‐β‐farnesene synthase ( EbFS ) gene is strongly expressed in inner cortex tissue surrounding the vascular system of the aphid‐preferred flower receptacle and peduncle, leading to elongated cells filled with EβF. Aphids that probe these tissues during settlement encounter and ingest plant EβF, as evidenced by the release in honeydew. These EβF concentrations in honeydew induce aphid alarm responses, suggesting an extra layer of this defense. Collectively, our data elucidate a defensive mimicry in pyrethrum flowers: the developmentally regulated and tissue‐specific EβF accumulation and emission both prevents attack by aphids and recruits aphid predators as bodyguards.